The biodiesel handbook - Knothe, Gerhard; Van Gerpen, Jon Harlan; Krahl, Jurgen, 1962- (AOCS Press, 2005)
Annotation Whether it is created as neat diesel fuel or in blends with petroleum-based diesel fuels, biodiesel represents a positive alternative to fossil fuels. Drawing on the expertise of researchers from around the world, The Biodiesel Handbook summarizes the legislative, chemical, and engineering issues that surround biodiesel and presents new data and technical information. The most up-to-date resource on biodiesel available, this book covers legislative and regulatory efforts around the world, the history of vegetable oil-based diesel fuels, the basic concept of the diesel engine, and glycerol, a valuable byproduct of biodiesel production.
Keywords: Biodiesel fuels.; elektronické knihy; electronic books